Three new species of Epipompilus Kohl (Hymenoptera, Pompilidae, Pepsinae) from Australia - Yuan, David; Rodriguez, Juanita (Zootaxa, 2020)
Three new species are added to the genus Epipompilus (Hymenoptera: Pompilidae) in Australia. Epipompilus mirabundus sp. nov., E. taree sp. nov., and E. namadgi sp. nov. are described and illustrated. A key to males of Epipompilus is provided. A novel association of Epipompilus and Sceliphron formosum (Hymenoptera: Sphecidae) is also documented. The larva of E. mirabundus sp. nov. was found sharing single nest cell with a Sceliphron larva; this association could be the result of a parasitised spider being brought back to the nest by the Sceliphron adult.